Effectiveness of Antiprotozoic Therapy in Hiv Infection with Intestinal Parasites - Mirkhamzaevna, Achilova Matlyuba (American Journal of Bioscience and Clinical Integrity, 2025)
This study investigated the effectiveness of antiprotozoal therapy in cases of HIV infection with intestinal parasitosis. For the study, 70 HIV-infected patients who applied for treatment to the Samarkand Regional Infectious Diseases Hospital and the Samarkand Regional AIDS Control Center in 2023-2024 were recruited. The patients studied were divided into 2 groups: 40 patients with HIV infection + intestinal parasitosis (intestinal giardiasis, amebiasis, blastocystosis) formed group I (main group) and 30 patients with HIV infection who did not have intestinal parasitosis during the examinations formed group II. This study used general clinical: patient complaints, history and objective; laboratory: coproovoscopy, serological and molecular genetic methods. According to the results of the study, HIV infection causes more dyspeptic symptoms in patients with intestinal parasitosis. Laboratory indicators show an increase in the number of eosinophils. It negatively affects the immune system of patients, causing a decrease in the number of CD4+ lymphocytes. In patients taking anti-intestinal drugs on the background of ART, a positive change in these indicators is observed.